Superposition relations of microfabrics in the northern hanging-wall block - Dias da Silva, Icaro F (2017)
This study reports alternation of D2 extension-related and D3 contraction-related microfabrics in the northern hanging wall block of a gneiss dome-like structure recognized in the Évora Massif (Ossa-Morena Zone). In the Arraiolos – Santo Antonio de Alcorrego traverse high- to low-grade mylonites are dominant. Microfabrics related to D2 ductile deformation and M2 high-amphibolite to greenschist facies characterize an extensional shear zone with telescoping metamorphic isograds. D2 microstructures indicate shear sense with top-to-SE. Superposition of D3 contraction developed under greenschist facies (M3) producing folding of D2 microfabrics, mylonitization of granites along strike-slip shear zones and retrogression of M2 mineral assemblages.